Strategi utusan kerajaan dalam menjalin hubungan diplomatik pada zaman kesultanan Melayu - Noor Muhammad, Salmah Jan (Penerbit Universiti Pendidikan Sultan Idris, 2014)
A country delegation must play an important role in emerging and forming a harmony relation between regional governments among regional governments. Therefore, this study used interaction approach introduced by Paul Watzlawick to explain diplomatic strategy and the strategy implementation method by the delegation especially when facing other government to help the governments represented to successful perform diplomatic relationship with other government. Apart from that, this study also used the legend of Hang Tuah’s manuscript as main discussion material.